2016
DOI: 10.7324/japs.2016.60508
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Stability-Indicating High Performance Thin Layer Chromatography (HPTLC) Method for estimation of Canagliflozin in bulk and Pharmaceutical Dosage Form

Abstract: The objective of the study was to develop and validate simple, authentic and stability indicating high performance thin-layer chromatographic method for determination of Canagliflozin in bulk and pharmaceutical formulations as per ICHQ2 R1 Guidelines. HPTLC aluminium plates Precoated with Silica Gel 60F254 using Toluene: Ethyl acetate: Methanol (2:2:1, v/v/v) as mobile phase were used for the chromatographic separation and it was validated with different parameters such as Linearity, Precision, Accuracy, Robus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…The main task of this work was to develop and validate eco‐friendly stability‐indicating HPLC and PLS methods for determination of canagliflozin along with its main degradation product as substituents for environmentally harmful reported HPLC methods which did not quantify or even structurally identify the resulting degradation product. The proposed HPLC method can be used as a substitute for the reported TLC–densitometric methods (Kaur, Wakode, & Singh, ; Emam, ) owing to the common advantages of HPLC over TLC–densitometry such as the high repeatability, accuracy, and short analysis time as well. On the other hand, a thorough literature survey showed that there is no reported chemometric method for determination of canagliflozin, making the proposed PLS method the first chemometric one for simultaneous determination of canagliflozin and its degradation product with high specificity and precision.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main task of this work was to develop and validate eco‐friendly stability‐indicating HPLC and PLS methods for determination of canagliflozin along with its main degradation product as substituents for environmentally harmful reported HPLC methods which did not quantify or even structurally identify the resulting degradation product. The proposed HPLC method can be used as a substitute for the reported TLC–densitometric methods (Kaur, Wakode, & Singh, ; Emam, ) owing to the common advantages of HPLC over TLC–densitometry such as the high repeatability, accuracy, and short analysis time as well. On the other hand, a thorough literature survey showed that there is no reported chemometric method for determination of canagliflozin, making the proposed PLS method the first chemometric one for simultaneous determination of canagliflozin and its degradation product with high specificity and precision.…”
Section: Resultsmentioning
confidence: 99%
“…A thorough literature survey showed canagliflozin determination by HPLC methods in a pharmacokinetic study ( Devineni et al, ), a pharmaceutical formulation (Kaur, Wakode, Singh, & Manachanda, ) in rat plasma (Iqbal, Ezzeldin, Al‐Rashood, Asiri, & Rezk, ; Iqbal, Khalil, Alanazi, & Al‐Rashood, ; Kobuchi, Yano, Ito, & Sakaeda, ; Dong et al, ), in human plasma (Iqbal, Ezzeldin, et al, ; Iqbal, Khalil, et al, ; Dudhe & Kamble, ; Saibaba, Pilli, Bimireddy, & Pandiyan, ; Udhayavani, Sastry, Rajan, Tejaswi, & Rajani, ), and along with metformin (Gaware, Patil, & Harole, ; Zaghary, Mowaka, & Hendy, ). Canagliflozin was also determined by spectrophotometric (Kaur et al, ; Kaur, Wakode, & Singh, ) and TLC–densitometric methods (Kaur, Wakode, & Singh, ; Emam, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported HPTLC-densitometric method [11] was based on using toluene which is not environmentally recommended [21] and also used methanol and ethyl acetate which are less preferable than acetone and ethanol from the environmental viewpoint [21].…”
Section: Greenness Profile Of the Suggested Methodsmentioning
confidence: 99%
“…In contrast, the proposed HPTLC-densitometric method studied method specificity through structural elucidation, quantification, and chromatographic separation of the degradation product from canagliflozin in one chromatogram in addition to the common advantages of TLC-densitometric methods over the reported HPLC methods [6][7][8][9][10]; being more cost effective and of higher sensitivity. Furthermore in spite of the stability indicating property of the reported TLC-densitometric method, [11] it was able to determine only canagliflozin degraded samples and the degradation was evidenced by the decrease in canagliflozin peak height which is not indicative and according to ICH guidelines [13], peak area must be considered for the change in drug concentration not peak height.…”
Section: Introductionmentioning
confidence: 99%